If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 + -5y + 12 + 16y = -6y + -18 Reorder the terms: 4 + 12 + -5y + 16y = -6y + -18 Combine like terms: 4 + 12 = 16 16 + -5y + 16y = -6y + -18 Combine like terms: -5y + 16y = 11y 16 + 11y = -6y + -18 Reorder the terms: 16 + 11y = -18 + -6y Solving 16 + 11y = -18 + -6y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '6y' to each side of the equation. 16 + 11y + 6y = -18 + -6y + 6y Combine like terms: 11y + 6y = 17y 16 + 17y = -18 + -6y + 6y Combine like terms: -6y + 6y = 0 16 + 17y = -18 + 0 16 + 17y = -18 Add '-16' to each side of the equation. 16 + -16 + 17y = -18 + -16 Combine like terms: 16 + -16 = 0 0 + 17y = -18 + -16 17y = -18 + -16 Combine like terms: -18 + -16 = -34 17y = -34 Divide each side by '17'. y = -2 Simplifying y = -2
| 4x-6=6x+3 | | 12x-2(4x-8)=28 | | 84(x+1)=(85+x)(x-1) | | 6(8-5x)+4=x+12 | | 2y-2=-1-2y | | 6y-1=2y+8 | | x=6x^2-9x | | 17y-19y= | | 2r+3s+12t=28 | | -4y-15=9y+11 | | 3x^2+11x-25=0 | | y(x-5)= | | x^2-22x+113=1 | | x^2-16x+48=33 | | -5x+45=11x+21 | | 3(3y-1)-3(2y)=1 | | 4(5+x)=44 | | x^3-5x=12 | | x^3-5=12 | | 5(y-3)=2y-27 | | 4+9z-2=7z+51-5z | | 124-2d=628 | | 24x^4+66x^3+36x^2= | | 2b+3=13 | | .1919191919= | | (X)x(1.00-.30)=320 | | (X)x(1.00-.30)=420 | | 5y-1.6=6y | | .5x+.41666667=.833333333 | | x(x+4)=25 | | 8r+8=36r+15 | | 2x^2+6x-4=-3x^2+14x |